NMR Pore Structure and Dynamic Characteristics of Sandstone Caused by Ambient Freeze-Thaw Action - Bo Ke; Keping Zhou; Hongwei Deng; Feng Bin (Shock and Vibration)
For a deeper understanding of the freeze-thaw weathering effects on the microstructure evolution and deterioration of dynamic mechanical properties of rock, the present paper conducted the nuclear magnetic resonance (NMR) tests and impact loading experiments on sandstone under different freeze-thaw cycles. The results of NMR test show that, with the increase of freeze-thaw cycles, the pores expand and pores size tends to be uniform. The experimental results show that the stress-strain curves all go through four stages, namely, densification, elasticity, yielding, and failure. The densification curve is shorter, and the slope of elasticity curve decreases as the freeze-thaw cycles increase. With increasing freeze-thaw cycles, the dynamic peak stress decreases and energy absorption of sandstone increases. The dynamic failure form is an axial splitting failure, and the fragments increase and the size diminishes with increasing freeze-thaw cycles. The higher the porosity is, the more severe the degradation of dynamic characteristics is. An increase model for the relationships between the porosity or energy absorption and freeze-thaw cycles number was built to reveal the increasing trend with the freeze-thaw cycles increase; meanwhile, a decay model was built to predict the dynamic compressive strength degradation of rock after repeated freeze-thaw cycles.